2022
DOI: 10.3389/fimmu.2022.1006076
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate and IL-10 concentration as predictors of long-covid in hemodialysis patients: A Brazilian study

Abstract: BackgroundThe global burden of persistent COVID-19 in hemodialysis (HD) patients is a worrisome scenario worth of investigation for the critical care of chronic kidney disease (CKD). We performed an exploratory post-hoc study from the trial U1111-1237-8231 with two specific aims: i) to investigate the prevalence of COVID-19 infection and long COVID symptoms from our Cohort of 178 Brazilians HD patients. ii) to identify whether baseline characteristics should predict long COVID in this sample.Methods247 communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…As a result, lymphocyte levels became significantly higher in COVID‐19 survivors with PCS ( n = 667) than without PCS ( n = 653) (SMD = 0.30; 95% CI: 0.12–0.48; Z = 3.26, p < 0.01), and heterogeneity was reduced ( I 2 = 51%, p < 0.05). For IL‐6, we removed the study of Correa et al 27 . due to potential source of funnel plot asymmetry, which turned IL‐6 levels to be significantly higher in COVID‐19 survivors with PCS ( n = 273) than without PCS ( n = 253) (SMD = 0.30; 95% CI: 0.12–0.49; Z = 3.17, p < 0.01), with no significant heterogeneity between studies ( I 2 = 6%, p > 0.1) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, lymphocyte levels became significantly higher in COVID‐19 survivors with PCS ( n = 667) than without PCS ( n = 653) (SMD = 0.30; 95% CI: 0.12–0.48; Z = 3.26, p < 0.01), and heterogeneity was reduced ( I 2 = 51%, p < 0.05). For IL‐6, we removed the study of Correa et al 27 . due to potential source of funnel plot asymmetry, which turned IL‐6 levels to be significantly higher in COVID‐19 survivors with PCS ( n = 273) than without PCS ( n = 253) (SMD = 0.30; 95% CI: 0.12–0.49; Z = 3.17, p < 0.01), with no significant heterogeneity between studies ( I 2 = 6%, p > 0.1) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…due to potential source of funnel plot asymmetry, which turned IL‐6 levels to be significantly higher in COVID‐19 survivors with PCS ( n = 273) than without PCS ( n = 253) (SMD = 0.30; 95% CI: 0.12–0.49; Z = 3.17, p < 0.01), with no significant heterogeneity between studies ( I 2 = 6%, p > 0.1) (Figure 3). For IL‐10, neutrophils, NLR, NT‐Pro‐BNP, platelets, troponin, and fibrinogen, we omitted studies that may be potential source of asymmetry in funnel plot, as well as studies with retrospective design or relatively low NOS score 27,31,34,40,43 ; however, levels of these biomarkers still remained non‐significant between COVID‐19 survivors with and without PCS (supplementary Figure ). For ferritin, monocytes, IFN‐γ, TNF‐α, and creatinine, no significant heterogeneity was present between studies, thus sensitivity analyses were not done.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an additional 5 articles were excluded because of the lack of clear, extractable data. Consequently, a total of 82 studies were ultimately selected for the meta-analysis, adhering to our established inclusion and exclusion guidelines (Townsend, Dyer et al 2020, Ahearn-Ford, Lunjani et al 2021, Aparisi, Ybarra-Falcón et al 2021, Colarusso, Maglio et al 2021, Gameil, Marzouk et al 2021, Loretelli, Abdelsalam et al 2021, Montefusco, Ben Nasr et al 2021, Ong, Fong et al 2021, Patterson, Guevara-Coto et al 2021, Peluso, Lu et al 2021, Soni, Soni et al 2021, Sun, Tang et al 2021, Taha, Samaan et al 2021, Utrero-Rico, González-Cuadrado et al 2021, Wallis, Heiden et al 2021, Wu, Deng et al 2021, Acosta-Ampudia, Monsalve et al 2022, Alfadda, Rafiullah et al 2022, Aparisi, Ybarra-Falcón et al 2022, Arslan, Aksakal et al 2022, Cervia, Zurbuchen et al 2022, Corrêa, Deus et al 2022, Díaz-Salazar, Navas et al 2022, Dugani, Mehta et al 2022, Durstenfeld, Peluso et al 2022, Elizabeth, Thomas et al 2022, Fan, Wong et al 2022, Fernández-de-Las-Peñas, Ryan-Murua et al 2022, Ferrando, Dornbush et al 2022, Flaskamp, Roubal et al 2022, Fogarty, Ward et al 2022, García-Abellán, Fernández et al 2022, Johannes, Andrea et al 2022, Kruger, Vlok et al 2022, Littlefield, Watson et al 2022, Magdy, Eid et al 2022, Martone, Tosato et al 2022, Meisinger, Goßlau et al 2022, Meltendorf, Vogel et al 2022, Nádasdi, Sinkovits et al 2022, Patel, Knauer et al 2022, Patra and Ray 2022, Peluso, Sans et al 2022, Petrella, Nenna et al 2022, Phetsouphanh, Darley et al 2022, Queiroz, Neves et al 2022, Saxena, Saxena et al 2022, Schultheiß, Willscher et al 2022, Sibila, Perea et al 2022, Simone, Caitlin et al 2022, Stavileci, Özdemir et al 2022, Taeschler, Adamo et al 2022, Wechsler, Butuci et al 2022, Wiech, Chroscicki et al 2022, Zhao, Schank et al 2022, Al-Hakeim, Abed et al 2023, Al-Hakeim, Al-Rubaye et al 2023, Al-Hakeim, Al-Rubaye et...…”
Section: Resultsmentioning
confidence: 99%
“…However, how COVID-19 specific metabolite, lipoprotein and inflammatory mediators relate to the severity of COVID-19 and LTCS outcomes remains poorly understood. Few studies suggested that mitochondrial dysfunction, impaired fatty acid metabolism and cytokine IL-10 production were greatly affected in LTCS patients [22; 26; 27]. Thus, the role of host metabolism and inflammation during the disease progression in LTCS individuals requires further investigation in refined patient cohorts from different geographical regions to validate common and different features of the disease.…”
Section: Introductionmentioning
confidence: 99%